HUBUNGAN KARAKTERISTIK PETANI DAN DUKUNGAN PENYULUH PERTANIAN DENGAN KEPUTUSAN INOVASI VARIETAS SANTANA PADA BUDIDAYA PADI SAWAH - Andri Amaliel Managanta; Ridwan Ridwan; Hikma Arsita (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
The Correlation of Farmer Characteristics and Agricultural Extensions Support with Decisions on Innovation Santana Varieties in Rice Cultivation. Innovation is a farmer's need if it can solve the problems that farmers are facing. This study was to determine the characteristics of farmers, the level of extension support and the process of adopting innovation in the Santana variety of lowland rice cultivation, and the relationship between the characteristics of farmers and the level of support of extension workers on the adoption rate of innovation in the Santana variety rice cultivation.The research was conducted from May to December 2020 in Tayawa Village Tojo District Tojo Una-Una Regency Central Sulawesi Province. The method used in this research is a survey method. The population of this study was 109 lowland rice farmers in Tayawa Village and 52 farmers as samples of lowland rice farmers.Data analysis used the Rank Spearman correlation test and was carried out to determine the level of perception of the characteristics of lowland rice farmers and extension support with innovation decision making in rice cultivation.The results showed that individual characteristics, including age, formal education level, non-formal education level, and land area, were not related to the innovation-decision for the Santana variety cultivation.The level of cosmopolitan one variable of farmer characteristics is significantly related to the decision of innovation in Santana variety cultivation. Weak extension processes have the potential to weaken the innovative decisions on the Santana variety cultivation. Increased levels of cosmopolitan and extension support to farmers in the form of interaction, problem-solving, and enhancing the cooperation with the group the potential to increase the use of varieties Santana. Keywords: extension, innovation decisions, varieties Santana ABSTRAK Inovasi menjadi kebutuhan petani apabila inovasi tersebut dapat memecahkan masalah yang sedang dihadapi petani. Penelitian ini untuk mengetahui karakteristik petani, tingkat dukungan penyuluh dan proses adopsi budidaya padi sawah varietas Santana, dan hubungan karakteristik petani dan tingkat dukungan penyuluh terhadap tingkat adopsi budidaya padi varietas Santana. Penelitian dilaksanakan bulan pada Mei hinggabulan Desember 2020 di Desa Tayawa Kecamatan Tojo Kabupaten Tojo Una-Una Provinsi Sulawesi Tengah. Metode yang digunakan dalam penelitian adalah metode survei. Populasi penelitian ini adalah petani padi sawah di Desa Tayawa sebanyak 109 petani dan sampel petani padi sawah yang digunakan sebanyak 52 petani. Analisis data menggunakan uji korelasi Rank Spearman dan dilakukan untuk mengetahui tingkat persepsi karakteristik petani padi sawah dan dukungan penyuluhan dengan pengambilan keputusan adopsi budidaya tanaman padi. Hasil penelitian menunjukkan karakteristik individu baikumur, tingkat pendidikan formal, tingkat pendidikan non formal dan luas lahan tidak berhubungan dengan keputusan inovasi budidaya varietas Santana. Tingkat kekosmopolitan satu variabel dari karakteristik petani yang berhubungan nyata dengan keputusan inovasi budidaya varietas Santana. Lemahnya proses penyuluhan berpotensi melemahkan keputusan inovasi budidaya varietas Santana. Peningkatan tingkat kekosmopolitan dan dukungan penyuluh berupa interaksi dengan petani, penyelesaian masalah dan peningkatkan kerjasama dengan kelompok berpotensi meningkatkan penggunaan varietas Santana. Kata kunci: penyuluh, keputusan inovasi, varietas Santana